The aesthetic calendar between Ibn Tabataba and Qadi al-Jurjani - حسن, لين; وضحى يونس (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
The Arabs, in their aesthetic criticism, meant beauty in everything they said, and they distinguished the good and the ugly based on foundations based on taste and the strength of the artistic sense, and this feeling is accompanied by a judgment of the aesthetic value of the work, Hence the tendency of the critics to consider the beauty latent in the form and its value due to the pleasure it achieves in the soul of the recipient through the mastery of expression and the beauty of photography. Aesthetic judgment links the aesthetic subject with tasting, and through this we see a unification between the connoisseur and the work of art, and to find this unification it is necessary to live with the work of art in order to perceive it aesthetically. This research seeks to study a fertile idea in ancient criticism, which is the aesthetic calendar, which is concerned with clarifying the places of good and bad, and working to improve the ugly by extrapolating two authors, namely, the caliber of poetry by Ibn Tabataba Al-Alawi The mediation between al-Mutanabbi and his opponents by Judge al-Jurjani, and the study of the elements and tools of aesthetic evaluation that the critics used to judge the value and beauty of the artwork.